1999
DOI: 10.1038/sj.ijo.0801046
|View full text |Cite
|
Sign up to set email alerts
|

Acute appetite reduction associated with an increased frequency of eating in obese males

Abstract: OBJECTIVE: To investigate the effects of altered feeding frequencies on the relationship between perceived hunger and subsequent food intake and appetite control in obese men. DESIGN: Obese men reported in a fasted state in the morning to the laboratory where an isoenergetic pre-load (4100 AE 234 kJ, which was 33% average daily energy requirement (ADER) of each subject) comprising 70% carbohydrate, 15% protein, and 15% fat was given. This was administered either as a SINGLE meal, or divided evenly over 5 meals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 35 publications
2
60
1
1
Order By: Relevance
“…A few experiments altered meal frequency during the experimental day and showed a greater appetite control with a higher meal frequency in lean 24 and obese men. 25 However, these are not directly comparable to the present study. We did not find any significant difference in fasting RMR across the four visits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A few experiments altered meal frequency during the experimental day and showed a greater appetite control with a higher meal frequency in lean 24 and obese men. 25 However, these are not directly comparable to the present study. We did not find any significant difference in fasting RMR across the four visits.…”
Section: Discussioncontrasting
confidence: 99%
“…3,6,[18][19][20][21][22][23] Studies considering appetite ratings derived from visual analogue scales (VAS) have been undertaken in lean 24 and obese. 25 In both cases, subjects were given a large breakfast on one occasion or 5 smaller meals at hourly intervals on the other. The total food intake through the morning was the same.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term changes have an immediate effect on food intake rhythmicity and, over time, the changes in rhythmic food intake lead to an increase in body weight. Higher calorie ingestion in the first part of the day determines changes in metabolism by increased satiation [25], improved insulin sensitivity [26], and reduced total daily energy intake [27]. It has been demonstrated that a time-restricted feeding regimen mice is a nonpharmacological strategy against obesity and associated diseases [28] and protects against obesity, hyperinsulinemia, and hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a greater appetite control was associated with a manipulated increased frequency of eating in lean males, 3 and acute appetite reduction was associated with a manipulated increased frequency of eating in obese males. 4 The combination of these data suggests that improvements in appetite control appear when energy intake is spread evenly over the course of a day.…”
Section: Introductionmentioning
confidence: 99%